2019
DOI: 10.1101/760215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining the adult hippocampal neural stem cell secretome: in vivo versus in vitro transcriptomic differences and their correlation to secreted protein levels

Abstract: Recent evidence shows that adult hippocampal neural stem and progenitor cells (NSPCs) secrete a variety of proteins that affect tissue function. Though several individual NSPC-derived proteins have been shown to impact cellular processes like neuronal maturation and stem cell maintenance, a broad characterization of NSPC-secreted factors is lacking. Secretome profiling of low abundance stem cell populations is typically achieved via proteomic characterization of in vitro, isolated cells. Here, we analyzed the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Sheddases are membrane-bound enzymes that cleave trans-membrane proteins, consisting of members from the ADAM, BACE and MMP protein families. Analysis of our own published single-cell RNA sequencing and liquid chromatography tandem mass spectrometry data from cultured adult DG NSCs revealed that multiple sheddases are detectable throughout the cell cycle and in quiescent NSCs, particularly Mmp15, Adam9, Adam10 and Adam12 (Figure 4B,C) (Denninger et al, 2020). Multiple sheddases were also detected in single cell RNAseq of in vivo DG RGL-NSCs from (Shin et al, 2015) (Figure 4D).…”
Section: Cell Surface Vegfr2 Is Cleaved By Sheddasesmentioning
confidence: 90%
“…Sheddases are membrane-bound enzymes that cleave trans-membrane proteins, consisting of members from the ADAM, BACE and MMP protein families. Analysis of our own published single-cell RNA sequencing and liquid chromatography tandem mass spectrometry data from cultured adult DG NSCs revealed that multiple sheddases are detectable throughout the cell cycle and in quiescent NSCs, particularly Mmp15, Adam9, Adam10 and Adam12 (Figure 4B,C) (Denninger et al, 2020). Multiple sheddases were also detected in single cell RNAseq of in vivo DG RGL-NSCs from (Shin et al, 2015) (Figure 4D).…”
Section: Cell Surface Vegfr2 Is Cleaved By Sheddasesmentioning
confidence: 90%
“…To begin investigating the role of EAATs in NSCs, we used cultured NSCs derived from adult male and female DG 26 . These cultures are composed primarily of quiescent and cycling NSCs when maintained in standard conditions 27 . Using our published bulk RNAseq and liquid chromatography tandem mass spectrometry data from these cells 27 , we first confirmed that cultured NSC expression of glutamate transporter and receptor genes was similar to that of in vivo NSCs, with EAAT1 being most abundant, followed by EAAT2, then lower but detectable expression levels of AMPA receptor subunits and metabotropic glutamate receptor transcripts (Fig S2A -C).…”
Section: Glutamate Stimulates Adult Nscs Via Eaat-mediated Transportmentioning
confidence: 99%
“…These cultures are composed primarily of quiescent and cycling NSCs when maintained in standard conditions 27 . Using our published bulk RNAseq and liquid chromatography tandem mass spectrometry data from these cells 27 , we first confirmed that cultured NSC expression of glutamate transporter and receptor genes was similar to that of in vivo NSCs, with EAAT1 being most abundant, followed by EAAT2, then lower but detectable expression levels of AMPA receptor subunits and metabotropic glutamate receptor transcripts (Fig S2A -C). We also confirmed that glutamate stimulated NSC proliferation, as revealed by incorporation of the thymidine analog ethynyl deoxyurdine (EdU) (Fig 2A ,D).…”
Section: Glutamate Stimulates Adult Nscs Via Eaat-mediated Transportmentioning
confidence: 99%
See 2 more Smart Citations